Experimental study of shallow flows over permeable rough bed - Nguyen, Ba Tuyen (2015)
This study focused on the hydraulic resistance, velocity distribution and turbulence structure of shallow open channel flows over permeable bed comprises of large-scale roughness, with remarkable insights on the effect of bed permeability and roughness submergence. It first presented a new and simple calculation for flow resistance coefficient and mean velocity, which showed a better performance compared to those currently available in literature, particularly for flows with the roughness submergence smaller than five. The study also proposed a useful approach, using the plane mixing layer analogy, to improve the scaling of mean velocity profiles in the outer region of the flows. To justify the newly proposed length and velocity scale, an eddy viscosity model was employed together with further validation using data available in literature. Finally, by utilizing the state-of-the-art non-intrusive measurement techniques, this study revealed the mechanics and distinctive features of turbulence in shallow flows over permeable rough bed.